Faktor Faktor Yang Memengaruhi Tingkat Pengetahuan Pemilihan Kontrasepsi Pada Pasangan Usia Subur : Literature Review - Feriani, Pipit; Alfizar, Faris; Yolanda, Elfa; Nabila, Nabila; Sanritamaya, Musdalifah Rara; Fitri, Fitri (Universitas Pahlawan Tuanku Tambusai, 2025)
Background: Contraceptive use is influenced by social, economic, educational factors, knowledge level, partner support, and the role of health workers in providing accurate information and family planning education. Objective: This literature review aims to identify the factors that influence the level of knowledge among couples of reproductive age in choosing contraceptive methods. Methods: Article searches on PubMed, ScienceDirect, and EBSCO yielded 2.647 articles. After applying inclusion criteria, 10 relevant articles were selected related to contraceptive knowledge among couples of reproductive age. Results: The 10 articles from various countries show that education, access to services, social, cultural, economic factors, and partner support influence the level of knowledge and contraceptive choices among couples of reproductive age. Conclusion: Family planning services are more effective when nurses understand the social and individual factors that affect couples’ knowledge and act as facilitators of behavior change and decision-making within the family.